If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+3)+3x=4(x+6)+1
We simplify the equation to the form, which is simple to understand
3(x+3)+3x=4(x+6)+1
Reorder the terms in parentheses
+(+3x+9)+3x=4*(x+6)+1
Remove unnecessary parentheses
+3x+9+3x=+4+*(+x+6+)+1
Reorder the terms in parentheses
+3x+9+3x=+(+4x+24)+1
Remove unnecessary parentheses
+3x+9+3x=+4x+24+1
We move all terms containing x to the left and all other terms to the right.
+3x+3x-4x=+24+1-9
We simplify left and right side of the equation.
+2x=+16
We divide both sides of the equation by 2 to get x.
x=8
| x^4+72x-20=0 | | 8x+12=68 | | 2+g=14 | | -4(-2+5)=6(x-3) | | 9n-(2n-3)=10 | | 44+55= | | 4y-10+y+54=8y+50-6y | | x-2y=21 | | -(10x+1)+3=-9+6x | | -4x+2=8x-26 | | 5x-7+x=4+5x | | 6x-6=4x+2 | | 20-n=10-2 | | 3x+x+1.5x+180=455 | | (n-1)(5n-2)=0 | | 3x+x+1.5+180=455 | | 5x-12=4x-14 | | -9x^2-48x+15= | | 3x-5=4+2x+8 | | w^2+w=0 | | w=7h+80 | | 5(y-2)=-2(12-9)+y | | 6(4-4)=3(8+3) | | 5x-(6x+(8-(x+1)))=-2x+1 | | 6(4x-4)=3(8x+3) | | m=160-15(6) | | [4x-6]=14 | | 3+16r-2=9r+78-4r | | 5(y-2)=-2(12-9y) | | (-x-1)(-6x+4)=2x*3x | | 3+16r-2=94+78-4r | | 3n+9n=96 |